85 rights groups demand end to Govt facial ID sales. (February 2019) - Unknown
Abstract : Biometric technology suppliers Microsoft, Amazon and Google have been urged by over 85 racial justice, faith and civil rights groups to stop selling their face recognition (FRT) systems to the US Government.